The COVID-19 pandemic and graduate studies stricto sensu in Brazil - Ribeiro, Daniella Borges (Argumentum, 2023)
This research describes the scene for graduate programmes stricto sensu in Brazil, from 2000 to 2021, highlighting the years of the COVID-19 pandemic. It is quantitative research developed through data collected from the CAPES Georeferenced Information System, which was analysed using descriptive statistical analysis. The results reveal the expansion of graduate programmes stricto sensu in Brazil, an increase in enrolments, and a reduction in the number of degrees completed during the COVID-19 pandemic.